Answer: Last option.
Step-by-step explanation:
In order to estimate the percent "n" of a number"x", you need easy numbers to work with, therefore you can round "n" and "x" up or down; but it is important to remember that this estimation does not give you an exact value.
You can observe that Sergei's first step was to round 149% and 67 up, getting this result:
[tex]=105[/tex]
To verify if this estimate is less or greater than the actual answer, we can find the actual answer. This is:
[tex]\frac{67*149}{100}=99.83[/tex]
Therefore, we can conclude that the estimate is greater than the actual answer because the percent and the number were both rounded up.
Answer:
D
Step-by-step explanation:
I did it on Edgen 2020
earth: 90 pounds; venus:
1.0730000000000000000000000000
I searched it up
6÷(7÷28)what is the answer?show work
Answer:
24
Step-by-step explanation:
6/(7/28)
6/(1/4)
6 * 4/1
6 * 4
24
Solve for n: -6(n -8) = 4(12 -5n) + 14n.
Answer:
infinite solutions
Step-by-step explanation:
Given
- 6(n - 8) = 4(12 - 5n) + 14n ← distribute parenthesis on both sides
- 6n + 48 = 48 - 20n + 14n, that is
- 6n + 48 = 48 - 6n ( add 6n to both sides )
48 = 48 ← True
This indicates that the equation is true for any value of n
Answer:
This is a very classical type of equation in which, the solution is basically any number and it is known as an "Identity". So it has infinite solutions
Step-by-step explanation:
Apply the distributive law to both sides of the equation:-6(n-8) = 4(12-5n)+14n
-6n-6*(-8) = 4*12+4*(-5n) + 14n
Reduce similar terms-6n+48=48-20n+14n
-6n+48=48-6n
From here it is clear them to see that by adding -48 and 6n to both sides one obtains the identity 0 = 0-6n+48=48-6n
-6n +6n + 48 -48 = 48 -48 - 6n + 6n
0 = 0
So every time you find this kind of problem and after reducen the equation you end up with a true statement, then the equation has infinite solutionsAm I right about this or..?
Answer:
Correct, as 4 is the only number repeating twice
Kai has a mass of 55kg. What would Kai weigh on Mars? (The gravitational field strength on Mars is 3.7N/kg). Give your answer to 1 decimal place.
Answer:
203.5 N
Step-by-step explanation:
Force = mass × acceleration
F = ma
F = (55 kg) (3.7 N/kg)
F = 203.5 N
The weight of the Kai on planet mars is 203.5 N.
WeightWeight can be defined as the heaviness of a person. Also, weight is the product of the mass of the object and the acceleration due to gravity (or gravitational field strength).
[tex]\rm{ Weight = mass \times gravitational\ field\ strength[/tex]
Given to usKai's mass = 55kg,gravitational field strength on Mars = 3.7N/kg,Kai's weight on Mars[tex]\rm{Kai's\ weight\ on\ Mars = Kai's\ mass \times gravitational\ field\ strength\ on\ Mars[/tex]
[tex]= 55 \times 3.7\\= 203.5\ N[/tex]
Hence, the weight of the Kai on planet mars is 203.5 N.
Learn more about Weight:
https://brainly.com/question/834594
PLEASE HURRY! DUE TOMORROW! Please answer all of these.
Answer:
1. C
2. C
3. A
Step-by-step explanation:
the sum of 3 and 13
Answer:
16
Step-by-step explanation:
The sum of 3 and 13 would look like this as an equation, 3 + 13 = ? Just add 3 to 13 and you get 16 as your answer.
Select the correct answer.
Lindy works at a pizza restaurant and gets a 10% employee discount. She knows that if she orders d drinks and a medium pizza with t toppings, her total cost can be found using this expression:
0.90(2.25d + 1.40t + 6).
What is the total cost for Lindy and her friends to order 4 drinks and a medium pizza with 3 toppings?
A.
$17.28
B.
$16.52
C.
$28.40
D.
$15.69
Answer:
A
Step-by-step explanation:
In the expression
[tex]0.90(2.25d+1.40t+6),[/tex]
d is the number of drinks Lindy orders;
t is the number of toppings Lindy orders.
If Lindy and her friends order 4 drinks and a medium pizza with 3 toppings, then d = 4 and t = 3. Find the value of the expression above when d = 4 and t = 3:
[tex]0.90(2.25\cdot 4+1.40\cdot 3+6)=0.90(9+4.20+6)=0.90\cdot 19.20=17.28[/tex]
So, Lindy and her friends will pay $17.28
Lindy's total cost for ordering 4 drinks and a pizza with 3 toppings amounts to $17.28, so the correct answer is Option A.
Explanation:First, we substitute the given number of drinks and toppings into the expression, resulting in 0.90(2.25*4 + 1.40*3 + 6). That simplifies to 0.90(9 + 4.2 + 6), which further simplifies to 0.90(19.2). Finally, we multiply 0.90 by 19.2 to get the total cost, that is $17.28, which implies the correct answer is Option A.
Learn more about Algebraic Expression here:https://brainly.com/question/953809
#SPJ3
Change .06 to a percent
Answer:
6 percent
Step-by-step explanation:
if the 6 was in the tenths place (1 to the left) it would be 60%, however it is in the hundreds place therefore its value is 6%
Final answer:
To convert 0.06 to a percent, multiply it by 100 to get 6%.
Explanation:
To change 0.06 to a percent, you multiply it by 100. Doing this moves the decimal point two places to the right.
Here's the step-by-step calculation:
Start with the decimal: 0.06
Multiply by 100: 0.06 × 100 = 6
The result is: 6%
So, 0.06 as a percent is 6%.
There are 28 students in class the ratio of girls to boys is 3:4. How many girls
Step-by-step explanation:
let the num be 3x & 4x
3x+4x=28
7x=28
x=28/7
x=4
now, num of girls=3x=3×4=12
& num of boys=4x=4×4=16
Answer: 12 girls
Step-by-step explanation: You first want to make this equation become a fraction with the number of girls on top and the total on bottom. This becomes 3/7. To make this over 28, multiply by 4 on the top and the bottom. This makes 12/28, making 12 girls the answer.
Solve the inequality.
2(4x - 3) _>-3(3x) + 5x?
0 x 20.5
OX22
(-0, 0.5]
(-0, 2]
Answer:
[tex]\large\boxed{[0.5;\ \infty)}[/tex]
Step-by-step explanation:
[tex]2(4x-3)\geq-3(3x)+5x\qquad\text{use the distributive property}\ a(b+c)=ab+ac\\\\(2)(4x)+(2)(-3)\geq-9x+5x\\\\8x-6\geq-4x\qquad\text{add 6 to both sides}\\\\8x\geq-4x+6\qquad\text{add}\ 4x\ \text{to both sides}\\\\12x\geq6\qquad\text{divide both sides by 12}\\\\x\geq\dfrac{6}{12}\\\\x\geq\dfrac{1}{2}\to x\in\left[\dfrac{1}{2};\ \infty\right)[/tex]
The question is about solving an inequality, but the actual inequality is not fully provided. General steps have been given to approach solving such problems, with a note that a specific solution requires the complete inequality. The student should provide the full inequality for a precise solution.
Explanation:The student is asking for help with solving an inequality problem. Without a complete and clear inequality provided, we are unable to give a full step-by-step solution. However, I can provide a general approach to solving linear inequalities:
First, combine like terms and simplify both sides of the inequality.Next, isolate the variable term on one side of the inequality.Finally, divide by the coefficient of the variable if necessary to solve for the variable, and don't forget to reverse the inequality sign if you divide by a negative number.If the student provides the full inequality, using these steps will lead to the solution, where you would then graph the solution set on a number line and use either parenthesis or brackets to denote whether endpoints are included (for 'greater/less than or equal to') or excluded (for 'greater/less than').
Learn more about Solving Inequalities here:https://brainly.com/question/26855203
#SPJ2
When you are finding mode, if two numbers appear the same amount of times, do you choose the greater number or not?
Answer:
Both of them are the mode
Step-by-step explanation:
Answer:
The number that appears the most
Step-by-step explanation:
No, you choose the number that appears the most.
(example) What is the mode of these numbers?
4,4,5,5,5,6,6
The mode would be 5 because it comes up the most
Y = 5x + 3 written in standard form
Answer:
5x - y = - 3
Step-by-step explanation:
The equation of a line in standard form is
Ax + By = C ( A is a positive integer and B, C are integers )
Given
y = 5x + 3 ( subtract y from both sides )
0 = 5x - y + 3 ( subtract 3 from both sides )
- 3 = 5x - y, that is
5x - y = - 3 ← in standard form
Which is the largest fraction? 7/13 or 6/13
Answer:
7/13
Step-by-step explanation:
more parts to the fraction
Answer:
[tex]\frac{7}{13}[/tex] > [tex]\frac{6}{13}[/tex]
Since both fractions have the same denominator, you can just compare through the numerator.
Hence, [tex]\frac{7}{13} > \frac{6}{13}[/tex]
Convert these unlike fractions to equivalent like fractions and add them. You must use the LCD to get the answer correct. If possible, reduce the final sum.
1/5+2/3
Answer: Find the lowest common denominator of the 2 denominators
Step-by-step explanation:
The common in both denominator is 15.
3: 3,6,9,12,15,18,21,24,27,30
5: 5,10,15,20,25.30,35,40,43,50
Since 5x3 is 15, 1/5 x 3/3= 3/15
Since 3x5 is 15, 2/3 x 5/5= 10/15
3/15 is equivalent to 1/5 and 10/15 is equivalent to 2/3.
3/15 + 10/15 is equal to 13/15
13/15 can't be simplified because they are both odd numbers and they have less than 2 factors.
Hope this helped! Have a nice day! :D
Final answer:
To add 1/5 and 2/3, you must find the LCD, which is 15, convert the fractions to have the same denominators, then add them to get the sum of 13/15.
Explanation:
To add the unlike fractions 1/5 and 2/3, we first need to convert them to equivalent like fractions using their Least Common Denominator (LCD).
Prime factorize the denominators: 5 is already a prime number, and 3 is also a prime number.
To find the LCD, we take the product of the different prime factors, which is 5 × 3 = 15.
Convert each fraction by multiplying by an appropriate form of '1' to get the same denominator: 1/5 = (1×3)/(5×3) = 3/15 and 2/3 = (2×5)/(3×5) = 10/15.
With like denominators, we can now add the fractions: 3/15 + 10/15 = 13/15.
The final answer, 13/15, is already in its simplest form and cannot be reduced further.
Can somebody please help me
Answer:
462 sq in
Step-by-step explanation:
3((14 2/3)(10.5))
3(154)
462
What is 913 rounded to the nearest hundred
Evaluate the expression. Write your answer as a fraction is simplest form. 4 3/4*5/6*-2 1/3=
The required value of the given expression would be fraction -9 17/72.
What is the fraction?A fraction is defined as a numerical representation of a part of a whole that represents a rational number.
The expression is given in the question
⇒ (4 3/4) × 5/6 × ( -2 1/3)
We have to evaluate the given expression,
⇒ (4 3/4) × 5/6 × ( -2 1/3)
⇒ (4 3/4) × 5/6 × (-1)(2 1/3)
⇒ (4 + 3/4) × 5/6 × (-1)(2 + 1/3)
⇒ (19/4) × 5/6 × (-1)(7/3)
⇒ 85/24 × (-7/3)
Apply the multiplication operation,
⇒ -665/72
Apply the division operation,
⇒ -9.236111
⇒ -9 17/72
Therefore, the required value of the given expression would be fraction -9 17/72.
Learn more about the fractions here:
brainly.com/question/10354322
#SPJ2
Final answer:
The expression 4 3/4 * 5/6 * -2 1/3 evaluates to -665/72 after converting mixed numbers to improper fractions and then multiplying the numerators and denominators. The result is in its simplest form.
Explanation:
The question involves evaluating a mathematical expression with mixed numbers and fractions and writing the answer in its simplest form. To solve this, we first convert mixed numbers to improper fractions. The expression given is 4 3/4 * 5/6 * -2 1/3. First, convert the mixed numbers:
4 3/4 = 4 + 3/4 = (4*4+3)/4 = 19/4-2 1/3 = -2 - 1/3 = (-2*3-1)/3 = -7/3Now multiply the improper fractions:
(19/4) * (5/6) * (-7/3)Multiply the numerators: 19 * 5 * (-7) = -665
Multiply the denominators: 4 * 6 * 3 = 72
Therefore, the result is -665/72. This is already in its simplest form as the numerator and denominator have no common factors.
Enter an inequality that represents the graph in the box.
Answer:
[tex]y>-3x+6[/tex]
Step-by-step explanation:
First find the equation of the "boundary line" that separates the two sections of the plane. It is very simple to find its slope_y-intercept form from the graph.
We can find the slope of the boundary line by examining the two points where it intersects the axes: It crosses the y-axis at (0,6) (0 for x, 6 units for y)
and also crosses the x axis at (2,0) (2 unites for x and 0 for y)
That means that from the y intersect crossing, in order to arrive at the x intersect crossing, one has to go:
2 units to the right (this is called "run")
and 6 units down (this is called "rise", but should be considered as a negative value because instead of "rising" is going down)
Therefore, the slope of the boundary line is: [tex]slope = \frac{rise}{run} = \frac{-6}{2} = -3[/tex]
We also see that the y-intercept is = 6 (the point at which the line crosses the y-axis.
Then, we can write the equation of the boundary line as:
[tex]y = -3 x + 6[/tex]
Now, the set of (x,y) points that are highlighted in the picture are those "ABOVE" the boundary line, that is those points where the y-value is greater than those defined by the boundary line. Since the boundary line is drawn with a dotted line, that indicates that those values corresponding to (x,y) values in the line itself should NOT be included.
We therefore arrive at an inequality that does not contain an equal sign (to preclude the actual (x,y) values in the line to be included). and which indicates that we want all the (x,y) points on the plane which have y-values greater than those define by the boundary line. That is:
[tex]y>-3x+6[/tex]
Simplify 4xy-2x+4x-8xy
Answer: -4xy + 2x
Step-by-step explanation:
4xy - 8xy = -4xy
4x - 2x = 2x
Answer:
2x - 4xy or 2x(1 - 2y)
Step-by-step explanation:
Simplify 4xy-2x+4x-8xy
We can start by rearranging the expression;
4xy-8xy -2x + 4x
Then we add or subtract numbers with the same variable
-4xy + 2x
We can further factorize the above since 2x is common between the two numbers, so we will factor out 2x
2x(-2y + 1)
This can be re-write as;
2x(1 - 2y)
48 decreased by twice a number
Answer:
48 - 2x
Step-by-step explanation
minus = decreased
2x= twice a number
The expression is 2n-48.
What is an Expression?An expression is a mathematical statement which consists of variables, constants and mathematical operators.
Let the number be n.
The expression formed form the sentence is
2n - 48
To know more about Expression
https://brainly.com/question/14083225
#SPJ2
if f(x)=3+x/x-3, What is f(a+2)
Answer:
f(a + 2)= (5 + a) / (a - 1) or f(a+2)= (a+5)/(a-1)
Step-by-step explanation:
f(x)=(3+x)/(x-3)
To evaluate f(a+2), simply replace the x with a+2
f(a+2) = (3 + a+2)/(a+2 - 3)= (a+5)/(a-1)
or
To answer items such as this, we directly substitute the a + 2 to the all the x's in the function:
f(a + 2) = (3 + a + 2) / (a + 2 - 3)
Simplifying the function generated above:
f(a + 2) = (5 + a) / (a - 1)
Step-by-step explanation:
f(x) = 3+x/x-3
Substituting x = a+2, we get
[tex]f(a + 2) = \frac{3 + (a + 2)}{(a + 2) - 3} \\ f(a + 2) = \frac{a + 5}{a - 1} [/tex]
which is the final answer.
Please mark Brainliest if this helps!
How can you use the distributive property to
compute 7(49)?
Answer:
343.
Step-by-step explanation:
7(49)
= 7(40 + 9)
= 7*40 + 7*9
= 280 + 63
= 343.
One eighth of a number is less than or equal to 3
Answer:
less than
Step-by-step explanation:
The number the question is referring to is any number that is less than or equal to 24, since one eighth of 24 or any number less than 24 would be less than or equal to 3.
Explanation:The question is asking for a value which, when divided by 8 (or one eighth of it), results in a number that is less than or equal to 3. This implies a linear inequality. We can solve this by:
Starting with the inequality: 1/8 * x <= 3Multiplying each side by 8 to isolate the x variable: x <= 3 * 8Doing the multiplication on the right side: x <= 24So the solution to this inequality is any number less than or equal to 24. In other words, the original number can be 24 or any number less than 24.
Learn more about Linear Inequality here:https://brainly.com/question/29068591
#SPJ3
Diners frequently add a 15% tip when charging a meal to a credit card. What is the price of the meal without the tip if the amount charged is 13.80. How much was the tip
Answer:
2.07
Step-by-step explanation:
I need a brainiest answer, will anyone help me.
Of course! Im here to help!
gcf of 150, 275 and 420
The greatest common factor (GCF) of 150, 275, and 420 is 25. It is the highest number that can divide all three numbers without a remainder and is found by identifying the common prime factors among them.
Explanation:The question is asking for the greatest common factor (GCF) of the numbers 150, 275, and 420. The GCF is the highest number that can divide all three numbers without leaving a remainder. To find the GCF, we can break down each number into its prime factors:
150 = 2 × 3 × 5 × 5275 = 5 × 5 × 11420 = 2 × 2 × 3 × 5 × 7the common factors for 150, 275, and 420 are 5 × 5, since these are the only prime factors that appear in all three prime factorizations. Consequently, the GCF of 150, 275, and 420 is 5 × 5, which equals 25.
a line passes through the point(-4,-6) and has a slope of 1/2 What is the
equation of the line?
Answer:
x-2y-8=0
Step-by-step explanation:
The equation of line is given by the relation
y-y1=m(x-x1)
where m is the slope
now, given x1=-4 and y1=-6 and the slope is 1/2.
substitute into the equation to get
y+6=1/2(x+4)
multiplying through with the L.C.M
which is 2
2(y+6)=1/2×2(x+4)
2y+12=x+4
making x the subject
x= 2y+8 hence the equation of the line is x-2y-8 =0
Final answer:
The equation of the line that passes through the point (-4, -6) with a slope of 1/2 is y = 1/2x - 4.
Explanation:
To find the equation of a line that passes through the point (-4, -6) with a slope of 1/2, we use the point-slope form of a line's equation which is y - y1 = m(x - x1), where (x1, y1) is a point on the line and m is the slope. In this case, the point is (-4, -6) and the slope m is 1/2.
Plugging in the values, we get:
y - (-6) = (1/2)(x - (-4))
Simplify the equation:
y + 6 = 1/2x + 2
To get the equation in slope-intercept form y = mx + b, we do:
y = 1/2x + 2 - 6
y = 1/2x - 4
So the equation of the line is y = 1/2x - 4.
Explain how u can turn 5,400 in hundreds
Answer:
54 hundreds
Step-by-step explanation:
The volume of a box of earrings is 216 cubic centimeters. What is the length of one edge of the box
Answer:
its 6
Step-by-step explanation:
because
6.6.6= 216
Answer:
6 centimeter is the length of one edge of the boxStep-by-step explanation:
Given : The volume of a box of earrings is 216 cubic centimeters.
To find : What is the length of one edge of the box.
Solution : We have given
Volume of a cubic box = 216 cubic centimeter .
Volume of cube = (side)³ .
(side)³ = 216 cubic centimeter .
On taking cube root both sides.
side = [tex]\sqrt[3]{216}[/tex].
Side = [tex]\sqrt[3]{6*6*6}[/tex].
Side= 6 centimeter .
Therefore, 6 centimeter is the length of one edge of the box.